A rare cause of intraabdominal tumor in childhood: Omental mesenteric myxoid hamartoma - Arzu Şencan; Hülya Tosun Yıldırım; Münevver Hoşgör (Elsevier, 2014)
Omental masses are rarely seen in childhood. Omental mesenteric myxoid hamartoma is a very rare and a new entity, first described by Gonzalez-Crussi et al. The tumor originates from the omentum and mesentery and presents as multiple nodules. It shares many morphologic features with inflammatory myofibroblastic tumor and therefore, may be considered as a variant of inflammatory myofibroblastic tumor. However, the clinical course and prognosis of this tumor is different. This rare and relatively new pathology in childhood, mimicking malign tumor and sharing many histopathological features with inflammatory myofibroblastic tumor, is presented to emphasize that it is a clinically different entity in terms of clinical picture and prognosis.